Membangun Lingkungan yang Mendukung Pertumbuhan dan Pembelajaran: Studi Kasus Sekolah Ramah Anak di SDIT AR-Rahmaniyah Depok - Imam Hasani; Hartin Kurniawati (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze how SDIT AR-Rahmaniyah Depok implements the concept of child-friendly school to create an environment that supports the growth and learning of all students, including those with special needs. Using an in-depth interview approach with various parties in the school, this study uncovers the main motivations behind the implementation of the concept, the specific policies implemented, as well as the challenges faced by the school in creating an inclusive and enjoyable learning atmosphere. It also explores the central role of teachers and the involvement of parents and communities in supporting inclusive education. It was identified that the success of the program is underpinned by effective communication, ongoing training and collaboration with various health and psychology professionals in supporting students' mental and emotional well-being. As such, this study offers a comprehensive insight into how schools can develop effective and sustainable inclusive practices and provides recommendations for improvement and future development to ensure all children can learn and grow in a safe, supportive and inclusive environment.